The risk of purchasing counterfeit product on the internet - Balogh, Zita; Mészáros, Katalin (Studia Mundi – Economica, 2021)
The internet became an indispensable sales channel that expands shopping opportunities beyond the conventional limitations of time and place. This has led to increases in the number of consumers purchasing online, the frequency of online purchases, and the value of the online purchases. Nevertheless, e-commerce requires the establishment of a secure environment to ensure online customers are protected. This research paper aims to discover whether customers perceive the purchase risk associated with counterfeit products via the Internet in light of relevant legislation and technical solutions. The paper also explores possible connections between various demographic factors and perceived risk. The current study is based on empirical data collected via a questionnaire. A review of the relevant literature and an analysis of global statistics on counterfeit products were also undertaken. Following the presentation of the results obtained, the current work concludes by delineating some methods used to combat the trade in counterfeit products. The study findings revealed that the risk extent of counterfeit products does not significantly depend on the gender or education-levels of consumers. From the generational perspectives to perceived risk, significant differences in online purchase frequency exist among baby boomers; the perceived risk of purchasing counterfeit products is lower for weekly e-shoppers than it is for consumers who shop online less frequently. An additional statistically significant discrepancy was found for family status when married respondents were compared to those living together in non-marital relationships.